Models of Local Governance - Miller, W. author. aut Link
IX, 270 p.
Keywords: From 1979 to 1997 Britain was a laboratory for experiments in local governance as the control and delivery of local services was switched from elected councils to appointed boards (quangos), private companies or self-management. This book is about four models of local governance: the traditional 'localist' model, the New Right's 'individual' model, the New Left's 'mobilisation' model, and government's own 'centralist' model. It tests them against public opinion as expressed in 2203 interviews with ordinary citizens, 788 with councillors, and 902 with members of appointed boards.